FOOD SECURITY AND NUTRITION MONITORING IN THE NEW GLOBAL AGENDA "SUSTAINABLE DEVELOPMENT GOALS - 2016-2030" (International Journal of Innovative Technologies in Economy, 2018)
The article investigated the current state of affairs in the monitoring and information provision of the food safety formation's and nutrition's areas in the early stage of implementation of 2030 Agenda for Sustainable Development in Ukraine and in the world. The article highlights the key problems associated with the measurement under monitoring progress towards the second objective of Sustainable Development Goals (SDG 2), which is to eliminate the hunger, food security providing, nutrition improving and sustainable agricultural development. Established key links both between SDG 2 and others SDGs, described the main problems of monitoring of achievements in improvement of food security and nutrition indicators. Established the problems of monitoring and information support of the food security formation at the national and global levels for the purpose of its’ unification in the future.